MUSCULOSKELETAL DISORDER ASSOCIATED WITH DEVICE USAGE AT THE TEACHER PROFESSION - Septadina, Indri Seta; Wardiansah; Fatimah, Nyimas; Fitri, Agita Diora (Fakultas Kedokteran Universitas Sriwijaya, 2025)
. One of the most common diseases in workers is musculoskeletal disorders. where the prevalence of musculoskeletal disorders in teachers is around 39% to 95%. Most teachers experience chronic musculoskeletal disorders and subjective complaints, one of which is pain in the upper limbs. Some studies show the relationship between gadgets and user posture can cause discomfort and fatigue in the hands, elbows, and shoulders. This article discuss about the use of gadgets in an unergonomic position often results in musculoskeletal complaints. Static loading by holding handheld devices or gadgets for long periods, often with unergonomic postures and excessive use of muscles in the upper limbs, is likely to contribute to myofascial pain syndrome in the muscles of the hands and arms, resulting in pain in the upper limbs.